Effect of a 'diagonal' intervention on uptake of HIV and reproductive health services by female sex workers in three sub‐Saharan African cities. Issue 7 (25th May 2018) - Lafort, Yves; Greener, Letitia; Lessitala, Faustino; Chabeda, Sophie; Greener, Ross; Beksinska, Mags; Gichangi, Peter; Griffin, Sally; Smit, Jenni A.; Chersich, Matthew; Delva, Wim
Abstract: Objectives: To enhance uptake of sexual and reproductive health (SRH) services by female sex workers (FSWs), we conducted an implementation study in which we piloted and tested context‐specific 'diagonal' interventions, combining vertical, targeted interventions with horizontally improved access to the general health services, in three cities in sub‐Saharan Africa. Methods: We collected indicators of SRH service uptake through face‐to‐face interviews with approximately 400 FSWs, pre‐ and post‐intervention, in Durban, South Africa; Tete, Mozambique; and Mombasa, Kenya, recruited by respondent‐driven sampling. Changes in uptake were tested for their statistical significance using multivariate logistic regression models. Results: In all cities, overall uptake of services increased. Having used all services for contraception, STI care, HIV testing, HIV care, cervical cancer screening and sexual violence, if needed, increased from 12.5% to 41.5% in Durban, 25.0% to 40.1% in Tete and 44.9% to 69.1% in Mombasa. Across cities, the effect was greatest in having been tested for HIV in the past six months which increased from 40.9% to 83.2% in Durban, 56.0% to 76.6% in Tete and 70.9% to 87.6% in Mombasa. In Tete and Mombasa, rise in SRH service use was almost entirely due to a greater uptake of targeted services. Only in Durban was there additionally an increase in the utilisation of general health services. Conclusion: SRH service utilisation improved in the short‐term in three different sub‐Saharan African contexts, primarily through vertical, targeted components. The long‐term effectiveness of diagonal approaches, in particular on the use of general, horizontal health services, needs further investigation.